Willingness to Falsely Take Blame among Friends: Closeness, Reporting Wrongdoing, and Identity. Issue 8 (3rd August 2018) - Willard, Jennifer; Burger, Carly
ABSTRACT: This study examined people's willingness to falsely take the blame for a friend's offense. We sought to identify whether friendship closeness and individual differences would predict false blame-taking. Participants were randomly assigned to think of either a close or casual friend engaging in driver negligence and indicated their willingness to falsely take responsibility. Although self-construal was unrelated to willingness, oneness mediated the relationship between friendship closeness and blame-taking willingness. Negative attitudes about reporting wrongdoing predicted a greater willingness, and men were more willing to take the blame than women. Results may help those in the legal system to better identify false confessions.